Business communication today - Bovée, Courtland L (Pearson, 2013)
Business Communication Today provides the cutting-edge communication coverage that prepares readers for real business practice. Understanding the Foundations of Business Communication; Applying the Three-Step Writing Process; Crafting Brief Messages; Supporting Messages with Quality Information; Planning, Writing, and Completing Reports and Proposals; Designing and Delivering Oral and Online Presentations; Writing Employment Messages and Interviewing for Jobs.